Implementasi Tujuan Hidup Sebagai Tujuan Pendidikan Di Ma'had Tahfizhul Qur'an Pekanbaru - Silaturahim, Rahmat (Pacsasarjana UIN Sultan Syarif Kasim Riau, 2023)
The learning process is a measure of the results of the efforts made by educators and students with all related factors. This study will describe how the implementation of educational goals in improving learning outcomes at MTs Patra Mandiri Palembang City. The research was conducted with a qualitative approach. The subjects of this study were the head of the foundation, the principal, the Islamic education teacher. The method of collecting data with in-depth interviews was assisted by the WhatsApp application and document searches and data analysis were carried out using descriptive analytics. The conclusion is that the implementation of MTs Patra Mandiri learning uses a concise curriculum model, namely the compaction of materials and mass. From the assessment of all learning at MTs Patra Mandiri, all problems related to competence. Therefore, these questions can be used as a measuring tool to see the learning objectives. However, there are some problems that have not met the objective criteria of learning because the tool specified is an objective exam. The process of product assessment and assessment is carried out in the learning-learning process (not in the final semester exam). Therefore, the processes and products cannot be carried out regularly to the students for the long term. Based on student scores in the final semester exams, the learning objectives at MTs Patra Mandiri have been achieved. Naturally, students have unique characteristics, namely having individual diversity from one another in various ways. This diversity can be manifested in the diversity of intelligence, talents, personalities, and physical conditions.